Western medicine - Loudon, Irvine (Oxford University Press, 1997)
The history begins in ancient Greece, where medical practice, under the auspices of Hippocrates and others, first looked past supernatural explanations and began to understand disease as a product of natural causes. It chronicles the slow growth of medical knowledge through the Middle Ages and the Renaissance, illuminating the work of figures such as Paracelsus, Vesalius, and William Harvey (who explained how blood circulates through the body). And it provides portraits of more modern figures like Louis Pasteur and Robert Koch (the fathers of bacteriology), Wilhelm Roentgen (the discoverer of x-rays), and Paul Ehrlich (who pioneered the use of chemicals to destroy disease-causing organisms)